Prevalence of generative artificial intelligence sexualized image usage by adolescents in the United States - Chad M. S. Steel (PLoS ONE, 2026)
The prevalence of generative artificial intelligence (GenAI) usage related to sexualized images amongst adolescents is a critical emerging research area. In this exploratory study, a nationally representative online survey of 557 English-speaking individuals aged 13–17 was conducted. Participants were asked about their consensual and non-consensual usage and interactions with sexualized GenAI images. The survey included questions on images created with nudification software as well as content creation software, and asked participants about their creation, sharing, and viewing of this content, as well as that of their peers. Use of nudification tools was widespread, with 55.3% (n = 308) of participants reporting having created and 54.4% (n = 303) having received at least one image. Reported victimization levels of participants was substantial, with 36.3% (n = 202) of individuals reporting having a non-consensual image created and 33.2% (n = 185) of individuals having had at least one image non-consensually shared. Usage was similar across demographic categories, though male participants had higher degrees of regular GenAI sexual image creation and distribution, both consensual and non-consensual. Policymakers need to consider the extensive usage and its normalization and consider educational interventions, and practitioners need to be aware of the high degree and nature of victimization occurring.